Analisis Pengaruh Keamanan Transaksi Elektronik Terhadap Kepercayaan Konsumen: Pendekatan Regresi Linier dalam Konteks E-Business - Hannah, Roudlotul Hannah (Maliki Interdisciplinary Journal, 2025)
This study employs a quantitative observational approach and linear regression analysis to assess the impact of electronic transaction security on consumer trust in the context of E-Business. The developed model effectively explains data variability, and the F-test confirms a significant relationship between electronic transaction security, particularly financial transaction security, and consumer trust. With an R2 of 0.816, this research explains approximately 81.6% of consumer trust variation. These findings provide crucial insights into understanding the factors shaping consumer trust in the complex landscape of E-Business.